Memperbaiki Kinerja Pemasaran Melalui Pelatihan Kewirausahaan, Riset Pasar, Dan Inovasi Produk - Maman Sulaeman; Hasan Fahmi Kusnandar; Ristina Siti Sundari (Universitas Muhammadiyah Sidoarjo, 2018)
The purpose of this research is to know and analyze the improvement of marketing performance through entrepreneurship training, market research, and product innovation at UMKM in East Priangan West Java Province. The research method used is survey method. Data collection was obtained through questionnaires and literature study. The population in this study is MSMEs in East Priangan West Java. Determination of sample using random counted 75 samples and data analysis used was path analysis. The results found that partially entrepreneurial training, market research and product innovation were able to improve marketing performance. Simultaneously entrepreneurship training, market research and product innovation can improve the performance of UMKM marketing in East Priangan of West Java province.